Las reducciones toledanas a pueblos de indios: aproximación a un conflicto - Carolina Jurado (Cahiers des Amériques Latines)
The quest of Toledan re-grouping into new towns («pueblos de reducción») becomes a main issue to understand the organization of ethnic groups and the construction of a new colonial andean territoriality. Focusing on the social segmentation and the territorial resignificance caused by the resettlement of the Macha group (Northern Potosi), this article offers a new approach to elucidate the identity and the simbolic transformations of certain colonial andean groups, that were contained in the Prehispanic Qharaqhara Federation.